1986
DOI: 10.1017/s0022029900033124
|View full text |Cite
|
Sign up to set email alerts
|

Potassium iodate-induced proteolysis in ultra heat treated milk during storage: the role of β-lactoglobulin and plasmin

Abstract: SummaryThe report that addition of KI03 (0·1 mm) to milk before ultra high temperature (UHT) treatment induces extensive proteolysis during subsequent storage at 37 °C was confirmed. None was produced by addition of H202 KMn04 or K2Cr207. The pH optimum for KI03-induced proteolysis was between 7·0 and 8·0 and the temperature optimum 37—45 °C. β-Casein was particularly susceptible and the proteolysis pattern was similar to that caused by indigenous alkaline milk proteinase (MPA, plasmin). Addition of plasmin to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Thermal inactivation of plasmin in milk is thought to be due to thiol-disulphide interchange reactions with β-Lg [11]. Scollard et al [26] reported that HP treatment at 600 MPa did not inactivate plasmin in phosphate buffer, but inactivated >95% of plasmin in a phosphate buffer containing 5 mg·mL -1 β-Lg, which suggests that HP-induced inactivation of plasmin is also linked to β-Lg.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal inactivation of plasmin in milk is thought to be due to thiol-disulphide interchange reactions with β-Lg [11]. Scollard et al [26] reported that HP treatment at 600 MPa did not inactivate plasmin in phosphate buffer, but inactivated >95% of plasmin in a phosphate buffer containing 5 mg·mL -1 β-Lg, which suggests that HP-induced inactivation of plasmin is also linked to β-Lg.…”
Section: Discussionmentioning
confidence: 99%
“…The peak areas of separated peptides were determined by integration. The gradient described by [12] was used to measure β-lactoglobulin denaturation, using the same HPLC system.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmin is relatively heat stable in simple buffer systems, but is greatly destabilised when heated in the presence of β-lactoglobulin, due to thiol-disulphide interchange reactions between the disulphide bonds within the enzyme structure and the exposed thiol group of denatured β-lactoglobulin [12,16]. This leads to greatly reduced plasmin activity in, for example, ultra-high temperature (UHT) milk [15].…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of plasmin on a s1 -, a s2 -and b-CNs in solution has been determined (see ; it has little or no activity on k-CN, b-lactoglobulin (b-lg) or a-la (in fact, denatured b-lg is an inhibitor; Grufferty & Fox, 1986). In milk, the principal substrate for plasmin is b-CN, from which it produces g 1 -(b-CN f29-209), g 2 -(b-CN f106-209) and g 3 -(b-CN f108-209) CNs and proteose peptone (PP)5 (b-CN f1-105/107), PP8 slow (b-CN f29-105/107) and PP8 fast (b-CN f1-29).…”
Section: Plasminmentioning
confidence: 99%